“He Could Become the Mentor of Any Little Prince, If He Had Studied Methodology”. Around Some Letters from a Preceptor in the Mid 19TH Century. The Bajetta-Cherubini Correspondence (1839-1840) - Pruneri, Fabio (Rivista di Storia dell’Educazione, 2023)
A brief but intense educational experiment took place between 1839 and 1840 in two states of Italy before the unification: Lombardy and Sardinia. This pedagogical experiment consisted of transferring the teaching practices in use in schools inspired by the so-called “normal method” of Austrian Lombardy to Savoy Sardinia. The protagonists were Francesco Cherubini, director of the Brera normal schools, and Canon Antonio Manunta, a convinced innovator of education on the island. The mediator between the two was a young man: Giuseppe Bajetta, already a collaborator of the Lombard lexicographer and in charge of initiating in Sardinia the simultaneous teaching method in use in Milan. The article is based on unpublished correspondence between the parties involved. The letters reveal both the desire to modernise the island through a new way of conceiving elementary education and the difficulty of implementing this ambitious reform programme, essentially due to the need for trained teachers. The letters in the appendix offer a lively and rare description of the difficult task of a preceptor in the first half of the 19th century.